Modern weapons and military equipment for issue 4-2021 - Vučković, Dragan M. (Vojnotehnički glasnik / Military Technical Courier, 2021)
Life extension: The UK moves ahead with Challenger 2 MBT overhaul. Russian army to get Sprut-SDM1 SPATG self-propelled anti-tank gun. France selects nuclear propulsion option for future aircraft carrier.